Contaminants of Emerging Concern on Microplastics Found in the Chrysaora chesapeakei of the Patuxent River, Chesapeake Bay, MD - Carol A. Smith; Natalie Drichko; Miranda Lorenzo; Saroj Pramanik (Microplastics, 2025)
Previously, we reported that microplastic volatile organic compounds are present within the Chrysaora chesapeakei of Chesapeake Bay, MD. In this study, we report the presence of contaminants of emerging concern (CECs) on the hydrophobic surface of microplastic (MP) particles extracted from the C. chesapeakei, detected by Raman spectroscopy and identified by Wiley’s KnowItAll Software with IR & Raman Spectral Libraries. C. chesapeakei encounters various microplastics and emerging contaminants as it floats through the depths of the Patuxent River water column. This study identifies subsuming CECs found directly on microplastics from within C. chesapeakei in the wild using Raman spectroscopy. Among the extracted microplastics, some of the emerging contaminants found on the different microplastics were pesticides, pharmaceuticals, minerals, food derivatives, wastewater treatment chemicals, hormones, and recreational drugs. Our results represent the first of such findings in C. chesapeakei, obtained directly from the field, and indicate C. chesapeakei’s relationship with microplastics, with this species serving as a vector of emerging contaminants through the marine food web. This paper further illustrates a relationship between different types of plastics that attract dissimilar types of emerging pollutants in the same surrounding environmental conditions, underscoring the urgent need for further research to fully understand and mitigate the risks that MPs coexist with contaminants.